Regional Approaches to Sustainable Development Goals Implementation in Education, Healthcare, Environmental Management and Urban Resilience - Zul Ilham (Pusbindiklatren Bappenas, 2025)
This issue presents a diverse and compelling collection of research that highlights how countries in Southeast Asia and Africa are advancing the United Nations Sustainable Development Goals (SDGs) through localized, context-specific strategies. As part of the Global South, these regions face complex and interconnected challenges including limited resources, governance hurdles, and persistent socio-economic inequalities that make SDG implementation particularly demanding. Yet, the studies featured here demonstrate innovative approaches in education, healthcare, environmental management, and urban resilience that offer valuable insights into the region’s evolving pathways toward sustainable and inclusive growth.